1999
DOI: 10.1046/j.1365-2435.1999.00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Allocation of nitrogen and carbon in leaves of Metrosideros polymorpha regulates carboxylation capacity and δ13C along an altitudinal gradient

Abstract: 1. Metrosideros polymorpha (O’hia), the dominant tree species in Hawaiian forest ecosystems, grows from sea level to treeline (2500 m). Consistent changes in its morphology and anatomy occur along this altitudinal/temperature gradient. Patterns of variation in photosynthetic gas exchange, leaf nitrogen content, nitrogen‐use efficiency, δ13C, and morphological and anatomical characteristics were determined across the elevational gradient. In addition, on‐line carbon isotope discrimination studies of high and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
125
3
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(155 citation statements)
references
References 17 publications
23
125
3
4
Order By: Relevance
“…6A). This finding agrees with field studies on elevation gradients suggesting that community-scale adaptations to decreasing temperature are more strongly expressed in foliar structure than in N concentration (40,41). Notably, decreasing forest canopy LMA in the Andes is known to occur in conjunction with decreasing canopy compositional and functional diversity (21,42).…”
supporting
confidence: 88%
“…6A). This finding agrees with field studies on elevation gradients suggesting that community-scale adaptations to decreasing temperature are more strongly expressed in foliar structure than in N concentration (40,41). Notably, decreasing forest canopy LMA in the Andes is known to occur in conjunction with decreasing canopy compositional and functional diversity (21,42).…”
supporting
confidence: 88%
“…In the literature, most studies that have examined photosynthetic capacity (A max ) over altitudinal gradients have kept temperature, humidity and light level constant in order to compare populations, but either (i) did not mention how they managed the CO 2 variable (Cordell et al, 1998;Rundel et al, 2003), or (ii) used constant CO 2 molar fraction (ppm or µmol mol −1 or µbar bar −1 ) instead of constant partial pressure (GonzalezReal and Baille, 2000;Yin et al, 2004). These studies found results similar to those of Treatment A in our study: no significant variations of A max along the gradient (Cordell et al, 1999;Körner and Diemer, 1987;Kumar et al, 2006). However, a few studies have showed either slight increases in A max with increasing elevation (Friend et al, 1989;Premoli and Brewer 2007) or a decrease (Kao and Chang, 2001;Zhang et al, 2005).…”
Section: Discussionmentioning
confidence: 53%
“…The main geophysical drivers along altitudinal gradients from an ecological point of view are temperature, air pressure, precipitation and radiation (Körner, 2008). Indeed, morphological, phenological and physiological changes allow trees to maintain a relatively high level of growth-related activity despite increasingly constraining environmental conditions towards high elevation (Cordell et al, 1999). The main physiological traits that control the carbon uptake and water loss in plants and generally vary according to elevation are photosynthesis and stomatal conductance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since seed reserves provide a large part of first-year seedling' nitrogen (Villar-Salvador et al 2010), a positive effect of seed size on leaf WUE is expected if seedlings from bigger seeds (i.e. with more reserves) have leaves with more nitrogen (Brookes et al 1980;Tripathi and Khan 1990), higher nitrogen concentration (Khurana and Singh 2004), and thus higher carboxylation capacity relative to stomatal conductance to water vapour (Cordell et al 1999). On the other hand, the microsite of seed dispersal affects leaf WUE in relation to the abundance of resources, such as water and light (Ehleringer and Cooper 1988).…”
Section: Introductionmentioning
confidence: 99%